2006
DOI: 10.2355/isijinternational.46.1210
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale Structure of Ferric Oxyhydroxide Formed from Fe–Si Alloy in Aqueous Solutions Containing Different Salts

Abstract: Quantitative X-ray structural analysis coupled with reverse Monte Carlo (RMC) simulation was performed for characterizing the atomic-scale structure of g-FeOOH (lepidocrocite) particles. These particles were formed by dipping pure iron or Fe-2mass%Si alloy into aqueous solutions containing Na 2 SO 4 or NaCl. The realistic atomic-scale structures of g-FeOOH particles were estimated by fitting ordinary interference functions through the RMC simulation technique. The results revealed that the fundamental FeO 6 oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Intermediate iron oxides such as GRs containing ferrous ions are considered to be formed in the inner rust layer, and they are oxidized in final corrosion products, in which alloying elements may influence the formation of different constituent species formed in corrosion products. [3,4] In practice, it has been shown that in an aqueous solution, GR is transformed to Fe 3 O 4 with a spinel structure or ferric oxyhydroxides such as γ -FeOOH and α-FeOOH by oxidation, [13] and the amounts of these products depend on the reaction conditions. [13,14] These studies showed that the formation of the species depends on the temperature, partial pressure of oxygen, and reaction rates.…”
Section: γ-Feoohmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermediate iron oxides such as GRs containing ferrous ions are considered to be formed in the inner rust layer, and they are oxidized in final corrosion products, in which alloying elements may influence the formation of different constituent species formed in corrosion products. [3,4] In practice, it has been shown that in an aqueous solution, GR is transformed to Fe 3 O 4 with a spinel structure or ferric oxyhydroxides such as γ -FeOOH and α-FeOOH by oxidation, [13] and the amounts of these products depend on the reaction conditions. [13,14] These studies showed that the formation of the species depends on the temperature, partial pressure of oxygen, and reaction rates.…”
Section: γ-Feoohmentioning
confidence: 99%
“…[3,4] In practice, it has been shown that in an aqueous solution, GR is transformed to Fe 3 O 4 with a spinel structure or ferric oxyhydroxides such as γ -FeOOH and α-FeOOH by oxidation, [13] and the amounts of these products depend on the reaction conditions. [13,14] These studies showed that the formation of the species depends on the temperature, partial pressure of oxygen, and reaction rates. As these reaction conditions are important to control the constituent species in the corrosion products of iron and iron-based alloys, further in situ X-ray diffraction experiments for clarifying the formation process of corrosion products must be useful.…”
Section: γ-Feoohmentioning
confidence: 99%